2022
DOI: 10.1186/s12879-021-06999-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic accuracy of monocyte distribution width and procalcitonin in sepsis cases in the emergency department: a prospective cohort study

Abstract: Background Early diagnosis and treatment of patients with sepsis reduce mortality significantly. In terms of exploring new diagnostic tools of sepsis, monocyte distribution width (MDW), as part of the white blood cell (WBC) differential count, was first reported in 2017. MDW greater than 20 and abnormal WBC count together provided a satisfactory accuracy and was proposed as a novel diagnostic tool of sepsis. This study aimed to compare MDW and procalcitonin (PCT)’s diagnostic accuracy on sepsis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The MDW is a parameter that describes the size distribution of circulating monocytes. Several studies have reported that the MDW can be used for the early diagnosis of sepsis in the ED [7,8,32,33]. Similarly, Şenlikci et al found that the MDW can be used to differentiate mild pancreatitis from nonmild pancreatitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…The MDW is a parameter that describes the size distribution of circulating monocytes. Several studies have reported that the MDW can be used for the early diagnosis of sepsis in the ED [7,8,32,33]. Similarly, Şenlikci et al found that the MDW can be used to differentiate mild pancreatitis from nonmild pancreatitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the potential association between MDW and sepsis using multivariate adjustment [35][36][37]. Recent papers focused on improving sepsis prediction through the combined use of MDW and other laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The value of MDW as a diagnostic tool has been investigated in sepsis and coronavirus disease (COVID‐19). 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 Increased MDW values are associated with both disorders; however, the mechanistic processes that underpin these observations remain less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte distribution width (MDW) is a parameter generated alongside full blood counts (FBC) in new generation haematology analysers. The value of MDW as a diagnostic tool has been investigated in sepsis and coronavirus disease (COVID‐19) 1–11 . Increased MDW values are associated with both disorders; however, the mechanistic processes that underpin these observations remain less clearly defined.…”
Section: Introductionmentioning
confidence: 99%